PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN VIDEO MATA KULIAH DASAR TATA RIAS PROGRAM STUDI PENDIDIKAN TATA RIAS DAN KECANTIKAN FT UNP - Murni Astuti (PAKAR Pendidikan, 2014)
The problem in this study was college students have difficulty to understanding the basic concepts of makeup and face shape correction in Makeup for Basic Make up course. This is indicated by the low student results obtained by students, and if this continues it feared would undermine the quality of education. The difficulty is thought to occur due to non optimal use of learning media by lecturers.Based on these problems is carried out through research efforts to develop learning media using video for Basic Makeup courses, that can help students understand the concepts and be able to practice in accordance with the concept.This research is the development of research. Model and procedure development using 4-D model (four - D model) consists of stages define, design, develop and disseminate. In the define phase analysis of curriculum and student analysis. In the design phase carried out using a video learning media in Basic Makeup course. At this stage of develop validated expertise and limited testing on students, to find out the practicalities and effectiveness of video media are developed. Phase disseminate not done. Researchers conducted a test of the media to see if the media produced valid, practical, and effective. The results of the data analysis showed that media video for Basic Make up, based learning using three criteria: (1) the terms of didactic 90.62% with very valid category, (2) construct terms 88.28% with very valid category, (3) technical requirements 95% with very valid category, the average percentage of 91.30% with very valid category. This suggests that the validity of the video media is in the category of very valid. Meanwhile, the average percentage of the practicalities of media by rating lecturers are 92.49%, based on test applicability media by students in small groups were 81.66% and based on the test applicability media by all students is 94.59%. Based on the test results of the practicalities of this media has been in the category of very practical. Based on test media effectiveness, student activity increased by 86,10% While the percentage success rate of student results that 88,88% of students have achieved the minimum 75. This means learning to use video media has been valid, practical and effective. It can be concluded that the use of learning media video in Basic Makeup course can be used as a medium of learning in Educational Studies Program Makeup and Beauty Faculty of Engineering, State University of Padang.